2011
DOI: 10.1016/j.neuron.2011.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Experience Dictates Stem Cell Fate in the Adult Hippocampus

Abstract: Adult hippocampal neurogenesis has been implicated in cognitive and emotional processes, and in response to antidepressant treatment. However, little is known about how the adult stem cell lineage contributes to hippocampal structure and function and how this process is modulated by the animal’s experience. Here we perform an indelible lineage analysis and report that neural stem cells can produce expanding and persisting populations of not only neurons, but also stem cells in the adult hippocampus. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
206
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(222 citation statements)
references
References 63 publications
13
206
2
1
Order By: Relevance
“…This is consistent with recent data showing IP expansion of neurogenesis in response to pathophysiological stimuli 54 . Similar to our previous findings that distinct NSC population respond to specific physiological stimuli 4 , the mode of increasing neuronal numbers may change under circumstances where rapid production of many neurons is required 54 . However, under normal conditions, the pool of NSCs requires 100 days before the number of newborn neurons exceeds their number.…”
Section: Hes5creersupporting
confidence: 94%
“…This is consistent with recent data showing IP expansion of neurogenesis in response to pathophysiological stimuli 54 . Similar to our previous findings that distinct NSC population respond to specific physiological stimuli 4 , the mode of increasing neuronal numbers may change under circumstances where rapid production of many neurons is required 54 . However, under normal conditions, the pool of NSCs requires 100 days before the number of newborn neurons exceeds their number.…”
Section: Hes5creersupporting
confidence: 94%
“…Mice iBax mice are homozygous for a loxP-flanked Bax allele (Takeuchi et al, 2005), hemizygous for a Nestin-CreERT2 transgene (Dranovsky et al, 2011), and maintained on a mixed C57BL/6 and 129/SvEv background, as previously described (Sahay et al, 2011). Although some ectopic expression has been reported in this transgenic line (Sun et al, 2014), it is unlikely to influence our phenotype since these ectopic cells are not undergoing apoptosis, and are therefore unlikely to be affected by the Bax deletion.…”
Section: Methodsmentioning
confidence: 99%
“…These cells are produced from progenitors located in the subgranular zone of the dentate gyrus, and their rates of proliferation, maturation, and survival are impacted by environmental conditions such as age, stress, exercise, and antidepressants (Dranovsky et al, 2011;Gould et al, 1997;Malberg et al, 2000;van Praag et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…RGL neural stem cells of the adult dentate gyrus also express astrocytic markers, but comprise a heterogeneous population based on the molecular markers they express, the morphologies they exhibit (17)(18)(19)(20)(21)(22), and their fate (23)(24)(25)(26)(27)(28). Nestin-GFP-positive RGL stem cells account for more than 70% of RGL stem cells in the SGZ of the dentate gyrus (24), but it was recently found that not all Nestin-GFP-positive cells with RGL morphology have stem cell properties (29): type β cells, which arborize in the granule cell layer (GCL) but do not reach the molecular layer (ML) of the dentate gyrus, account for 26% of Nestin-GFP-positive RGL stem cells.…”
mentioning
confidence: 99%